Teaching modules for developing reflective thinking in the social studies - Malicdem, Melanio Doria 1936- (1979)
This paper is primarily concerned with what instructional pattern can be adopted in the social studies in teaching students to think reflectively. This work was limited to social studies instructional procedures obtained in the secondary level of the two public and two private colleges in Abra. Interviews, class observations and a questionnaire were employed in the study. It was concluded that the modules on reflective thinking eased some of the teacher's burden, while students are allowed to work on their own. They are free to choose and assume responsibility for their decisions.
Vita.
Thesis (M.A. Social Studies Education)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Secondary) -- Philippines -- Abra; Social science teachers -- Philippines -- Abra; Teaching -- Aids and devices